Financial accounting : volume 1 part 1 - Valix, Conrado T.; Peralta, Jose F.;Valix, Christian Aris M. (Recto, Manila : GIC Enterprises & Co. Inc., 2015)
Volume one is in conformity with the undergraduate course syllabus for Financial Accounting I as promulgated by the Commission on Higher Education through the recommendation of the Board of Accountancy.
1. The accountancy profession -- 2. Conceptual framework -- 3. Qualitative characteristics -- 4. Elements of financial statements -- 5. Statement of financial position: An introduction -- 6. Statement of comprehensive income: An introduction -- 7. Cash and equivalents -- 8. Bank Reconciliation -- 9. Proof of cash -- 10. Accounts receivable -- 11. Estimation of doubtful accounts -- 12. Notes receivable -- 13. Loan receivable -- 14. Pledge, assignment and factoring -- 15. Discounting of note receivable -- 16. Inventories -- 17. Inventory cost flow -- 18. Lower of cost and net realizable value -- 19. Biological assets -- 20. Gross profit method -- 21. Retail inventory method -- 22. Financial asset at fair value -- 23. Investment in equity securities -- 24. Investment in associate -- 25. Financial asset at amortized cost -- 26. Effective interest method -- 27. Investment property -- 28. Fun and other investments -- 29. Derivatives -- 30. Forward, future, option and foreign currency.
Keywords: ACCOUNTANCY